2009
DOI: 10.1080/15332980902932441
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Problems on Behavior Problems in Adolescents and Adults With Autism Spectrum Disorders: Implications for Maternal Burden

Abstract: Recent research on individuals with autism spectrum disorders (ASD) highlights that they may be at increased risk for health problems when compared to the general population, and that these differences appear to increase with age. Relatively little research has examined the psychosocial impact of poorer health in this population, even though the clinical literature suggests that health problems put individuals with ASD at risk for elevated behavioral problems and their mothers at risk for elevated caregiving b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Since worse physical illness is often associated with elevated caregiver anxiety (45) and overall burden, (13, 46, 47) we analyzed symptom severity for all children to ensure that there were no significant group differences in asthma morbidity. Asthma symptom severity was assessed using the National Heart, Lung, and Blood Institute (NHLBI) guidelines for asthma control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since worse physical illness is often associated with elevated caregiver anxiety (45) and overall burden, (13, 46, 47) we analyzed symptom severity for all children to ensure that there were no significant group differences in asthma morbidity. Asthma symptom severity was assessed using the National Heart, Lung, and Blood Institute (NHLBI) guidelines for asthma control.…”
Section: Methodsmentioning
confidence: 99%
“…prevalence of primary caregiver that self-identifies as a smoker, prevalence of smokers in the home) and an objective measure (child’s salivary cotinine (49)). Additional covariates included basic demographic information such as caregiver age (5053) (<30 or ≥ 30 years), race (53) (White, Black or Other), ethnicity (53, 54) (Hispanic or not Hispanic), marital status (53, 55) (married/domestic partner or single), education (53) (<high school or ≥ high school), and dichotomized child asthma symptom severity (13, 46, 47) (mild persistent or moderate/severe persistent symptoms).…”
Section: Methodsmentioning
confidence: 99%
“…Past research has explored possible reasons for the elevated levels of psychological distress observed among parents of children with ASD, documenting several contributing factors including the core symptoms of autism (e.g., social difficulties, communication difficulties, and repetitive behaviors), delays in adaptive behavior, and co-occuring physical and mental health problems (Bishop et al, 2007; Cadman et al, 2012; Kring et al, 2008, 2010; Tomanik, Harris, & Hawkins, 2004). The majority of studies have consistently found that challenging behavior problems are among the most significant sources of stress for families (Hastings et al, 2005; Herring et al, 2006; Lounds, Seltzer, Greenberg, & Shattuck, 2007), highlighting how educational interventions to address child behavior likely will have cascading benefits for family life and parent stress.…”
Section: The Needs Of Families During Transitionmentioning
confidence: 99%
“…; Essex & Hong ; Kring et al . ; Lin ). Investigating how this behaviour impacts parent well‐being is particularly important as behaviour problems among adults with intellectual and/or developmental disability are common, with prevalence as high as 51.8% (Crocker et al .…”
Section: Introductionmentioning
confidence: 99%